Colorimeter construction of a low cost for use in agricultural product - Mota, Jedman Dantas; Queiroz, Alexandre José de Melo; Figueirêdo, Rossana Maria Feitosa de; Sousa, Karla dos Santos Melo de (Comunicata Scientiae, 2015)
This work aimed to build a low cost colorimeter was constructed, whose operation principle consists of determining a sample reflectance respecting a White Standard and compute the coordinates of L*a*b* color space using the CIE (Comission Internationale d’Eclairage – International Illumination Commission) equations. The equipment was constructed with wood pressed, and operates with 21 LED’s divided into 7 groups according to their color. The sensor has a similar response to the human eye is ideal for applications in photometry. The performance of the instrument was compared to a commercial model CR-10, in which a linear relationship was obtained between the chromaticity coordinates of the two units, with the calibration performed with 60 samples of colored powder.